Effectiveness of acute in-hospital physiotherapy with knee-extension strength training in reducing strength deficits in patients with a hip fracture: A randomised controlled trial. - Lise Kronborg; Thomas Bandholm; Henrik Palm; Henrik Kehlet; Morten Tange Kristensen (PLoS ONE)
Question Is acute in-hospital physiotherapy with additional progressive knee-extension strength training (ST) of the fractured limb more effective in reducing knee-extension strength deficit at follow-up compared to physiotherapy without strength training in patients with a hip fracture? Design Assessor blinded, randomised controlled trial with intention-to-treat analysis. Participants 90 patients with a hip fracture admitted to an acute orthopaedic Hip Fracture Unit at a university hospital between October 2013 and May 2015. Intervention Daily physiotherapy with or without progressive knee-extension strength training (10RM), 3 x 10 repetitions, of the fractured limb using ankle weight cuffs conducted by ward physical therapists during hospital stay. Outcome measures Primary outcome was the change in maximal isometric knee-extension strength in the fractured limb in percentage of the non-fractured limb from inclusion to postoperative day 10 or discharge (follow-up). Secondary outcome was Timed Up and Go test measured early after surgery and at follow-up. Results In the intention-to-treat analysis of between-group differences, the primary outcome improved 8.1% (95% CI -2.3; 18.4) by additional strength training from baseline to follow-up. In the per-protocol analysis of non-missing data, significant between-group improvements by 10.5% (95% CI 0.3; 20.7) were found in favour of additional ST. No significant between-group differences were found in any secondary outcome. Conclusion Physiotherapy with addition of 5 sessions of ST yielded no additional improvements compared to physiotherapy without strength training in reducing the knee-extension strength deficit at follow-up in patients with a hip fracture. It is debatable whether larger improvements than the observed 8-10% can be expected given that only five exercise sessions, on average, were completed. In fragile patients with a hip fracture in the acute phase, where the ability to participate in functional exercise is compromised, we still consider early strength training a possibility to improve outcomes of clinical importance, given the results of the per-protocol analysis. The present data provides an important basis and call for future investigations including longer term interventions. Trial registration Clinicaltrials.gov NCT00848913.